Measuring students’ understanding of statistical concepts using Rasch Measurement - Abu Kassim , Noor Lide; Ismail, Nor-Zatul Iffa; Mahmud, Zamalia; Zainol, Mohammad Said (International Association of Computer Science and Information Technology Press (IACSIT), 2010)

(untitled)
This study investigates students’ conceptual knowledge and understanding of basic statistical concepts and compares it against statistical competence, which is associated with discrete statistical knowledge and basic interpretive skills. It particularly examines the correspondence between students’ perceived ability and their empirical understanding of the concepts. Two instruments were developed: a 20-item test to measure students’ empirical understanding of the basic statistical concepts and a questionnaire with matching items to measure their perceived ability of these concepts. For a direct comparison of the two, students’ responses to the test and questionnaire items were jointly analyzed using the Rasch measurement model. Results of the analysis show that conceptual understanding of basic statistical concepts is more difficult to attain than statistical competence. The results also suggest that students more often than not overestimated their understanding of basic statistical concepts, particularly those requiring conceptual understanding of the concepts.